Action of cultural food practices in Pará AIMED at the nutrition of heart disease patients in northern Brazil: An experience report - Guterres, Aldair da Silva; Coutinho, Dalva Bastos e Silva; Torres, Rosileide de Souza; Valentim, Camila Queiroz; Reis, Adryele Aynara Brabo dos; Saraty, Jeane Kelly Tavares; Marques, Shirley Pascoal dos Reis; Aguiar, Marília Magalhães; Santos, Lorena Costa dos; Monteiro, Tília de Sousa; Barreira, Vanessa dos Santos; Ferreira, Andressa Gonçalves (Seven Editora, 2023)
Introduction: Nutrition education is a health education activity that greatly facilitates the dissemination of knowledge to hospitalized patients, since they generally have no interest in or direct access to information about healthy eating habits. Objective: To educate patients and carers about the nutritional value of açaí in order to minimize myths and doubts about its consumption. Methods: This was a descriptive study reporting on the experience of an educational activity carried out by nutrition interns/researchers and nutritionists at the State Public Foundation Hospital de Clínicas Gaspar Vianna (FPHCGV) in the city of Belém do Pará/Brazil, in March 2023. Results: Each participant was served 200 ml of açaí and 15 g of tapioca flour. After the tasting, an observational survey was carried out, where it was possible to verify that the action represented a satisfactory initiative with excellent acceptability. Conclusion: The action showed positive feedback on the acceptability of the food by the patients and a good understanding of the educational content provided. DOI:https://doi.org/10.56238/innovhealthknow-046